Clinical Efficacy and Safety of Eculizumab for Treating Myasthenia Gravis - Xiao, Hai; Wu, Ka; Liang, Xiaoliu; Li, Rong; Lai, Keng Po (Frontiers in Immunology, 2021)
Myasthenia gravis (MG) is an autoimmune disease primarily mediated by acetylcholine receptor antibodies (AChR-Ab), cellular immune dependence, and complement system involvement. Since the AChR on the postsynaptic membrane is destroyed by an immune attack, sufficient endplate potential cannot be generated, resulting in the development of a synaptic transmission disorder at the neuromuscular junction and in muscle weakness. The role of the complement system in MG has been demonstrated in animal models and clinical tests, and it has been determined that complement inhibition in patients with MG can prevent disease induction and reverse its progression. Eculizumab is a humanized monoclonal antibody that inhibits the cleavage of complement protein C5 and prevents autoimmune damage; additionally, it has received subsequent approval by the Federal Drug Administration of the United States for MG treatment. However, various concerns regarding the use of eculizumab persist. In this review, we have discussed the treatment time, cost effectiveness, long-term efficacy, and tolerability of eculizumab for MG treatment. We have also summarized historical information and have presented perspectives on this new therapeutic modality.